Les coulisses de la pensée économique de John Rawls - Rima Hawi (Œconomia)
This article deals with Rawls’s relationship to economics in the light of published texts and personal archive through three sequences, three periods of Rawls’s theory. A sequence where post-World War II liberalism seeks to reinvent itself and where Rawls exchanges with economists on unfinished versions of A Theory of justice. A period of enthusiasm, of convergences. A sequence around the published work (1971), where liberals doubt the finished version of A Theory, its principles of justice. This is a period of worry, controversies. A last sequence where Rawls is invited to explain himself. This is the time during which the philosopher tries to convince economists to work to reduce inequalities, to improve the situation of the least advantaged members of the society. In this sequence, we exploit an unpublished archive: Rawls’s document in preparation for his presentation to the American Economic Association, in 1974. Going into the economic thought of Rawls shows that behind the scenes, the philosopher is more of an economist than it seems, commenting Atkinson “maximin taxation”, situating his theory beyond, what he calls, “neoclassical welfare economics”.